Development of Sea Sand Therapy Requirement Questionnaire as an Instrument for Studying Sea Sand Therapy Model - Nur'aeni, Nabyla; Anggraeni, Santi Rukminita; Nursiswati, Nursiswati (Universitas Padjadjaran, 2024)
Several alternative and complementary health therapy techniques have known benefits in supporting the healing of various health problems. One of them is sea sand therapy. Indonesia has many beaches frequently visited by tourists, some of whom come for health therapy purposes. However, there are no studies or procedures that can be used to measure the preferences and needs of individuals to get sea sand therapy. The purpose of this study is to develop an instrument that can measure the tendency of individuals to do and benefit from sea sand therapy. Research on the development of procedures and the Sea Sand Therapy Requirement Questionnaire was conducted using quantitative methods with a descriptive design. The Sea Sand Therapy Requirement Questionnaire was tested using content testing by experts, face validity testing by respondents, and validity and reliability of construction testing by researcher. The questionnaire was tested on 60 respondents at Kejawanan Beach, Cirebon City selected based on inclusion criteria. The test results showed good validity for all questions compiled. This was indicated by the results of value r-count test which exceeds the predetermined r-table value of 0.254, and the results of the reliability measurement which shows a Cronbach's Alpha value of 0.759. Thus, Sea Sand Therapy Requirement Questionnaire is valid and reliable as an instrument to measure the tendency of individuals to get sea sand therapy and can be used for related services and research.Keywords: Reliability, validity, measurement instruments, complementary and alternative medicine, sea sand